Analisis Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Sekolah Menengah Atas - Ester Tiwery; Michael Alan Hirdi Pukada; Ester Uru Hida; Oriyanto Eks Enus (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2025)
This study aims to describe the management of the School Operational Assistance Fund (BOS) at SMA Negeri 13 Southwest Maluku. The management of BOS funds has an important role in supporting the smooth running of school operations, especially to help students from underprivileged families. The research method used was descriptive qualitative with interview, observation, and documentation approaches. The research subjects included the school principal, BOS treasurer, school committee, and teachers involved in BOS management. The results showed that budget planning was conducted through the preparation of the School Work and Budget Plan (RKAS) that involved all related parties. BOS funds were disbursed in two stages per year, namely in January and July, with details of the use of the budget that had been adjusted to the technical guidelines. The bookkeeping of BOS funds was done carefully, including the general cash book, bank assistant book, and tax assistant book. Supervision and evaluation were conducted by internal and external school parties to ensure transparency and accountability. Overall, the management of BOS funds at SMA Negeri 13 Maluku Barat Daya is running well, although it still requires additional assistance from the provincial government and contributions from parents to fulfill the school's operational needs.